A cidade em letras: uma análise da construção de Fortaleza no final do século XIX, no romance A afilhada de Oliveira Paiva - Parente, Tiago Coutinho (2009)
This dissertation seeks to analyze the literary construction of Fortaleza from the perspective presented in the novel A Afilhada, written by Oliveira Paiva, an author of the Brazilian state of Ceará, which was wrote in footnotes of Libertador, an abolitionist newspaper, published in the 1880’s, at Ceará. Basically forgotten by the history of Ceará’s literature, the novel makes a curious profile of a city in an initial process of modernization, at the end of the XIX century. The work is divided in three chapters. In the first moment, I seek to present historical aspects of the studied novel, its creation context, as well as I present some elements of economical and cultural transformations that Fortaleza city was passing through in the period characterized in the novel. I add these information to my theoretical-methodological referential. At the second chapter, I discuss the relation between the intellectual and the modern city and between this and the emergence of the novel, as well I present a summary defense about the importance of the narrative. Besides, at the second chapter, I do a brief comparison between the novel A Afilhada and A Normalista. The last one, written by another author of Ceará, Adolfo Caminha, was published in 1893. I argue that, although they are contemporaries, they construct similar cities, but with significant distinctions. At the third chapter, I present an intellectual profile of Oliveira Paiva, who participated in important publications in the history of Ceará literary-scientific production. Through the writing, as a disseminator of ideas and ideals, he made effort to transform the province in a place more civilized and close to the modernity. A lover of the science and the letters, Oliveira Paiva believed knowledge and words compose the two main weapons to eliminate the ignorance and delay presents in the city. Although fragments of the novel A Afilhada are present in almost the entire dissertation, at the third chapter I analyze more substantively the continent of the book. I defend the hypothesis that the city constructed by Oliveira Paiva is marked by an excess of natural elements that interferes in his possibility of ascension. Part of population, like the protagonist, doesn’t follow the grow of the modern city. The Fortaleza of Oliveira Paiva lacks also of citizens compromised to take care of the city like a father takes care of his daughter.